2018
DOI: 10.1186/s13717-018-0126-8
|View full text |Cite
|
Sign up to set email alerts
|

Land use change in highland area and its impact on river water quality: a review of case studies in Malaysia

Abstract: The policy of encouraging agriculture and development for mass tourism has led to environmental problems in Cameron Highlands, Malaysia. Rampant development and land clearing have significantly altered the land cover of Cameron Highlands for the past 30 years. Sensitive highlands areas are prone to landslides and soil erosion which then contributed to the main water pollution issues in the network of river system, sedimentation and siltation. The continuous trend of river water quality deterioration in Cameron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(67 citation statements)
references
References 30 publications
1
56
0
Order By: Relevance
“…As such, many studies have been conducted to address these problems; therefore, this research was necessary to accommodate the main findings of those previous studies, in order to facilitate researchers to identify specific areas requiring improvements and priorities. Razali et al (2018) reviewed case studies of land use change in highland areas and its impact on river water quality, and their study was limited to the river system network in the Cameron Highlands in Malaysia. However, the purpose of the present research was to review and analyze the main relationships between land use and water quality, as well as to visualize the major sources and processes of water quality pollution in Malaysia.…”
Section: Introductionmentioning
confidence: 99%
“…As such, many studies have been conducted to address these problems; therefore, this research was necessary to accommodate the main findings of those previous studies, in order to facilitate researchers to identify specific areas requiring improvements and priorities. Razali et al (2018) reviewed case studies of land use change in highland areas and its impact on river water quality, and their study was limited to the river system network in the Cameron Highlands in Malaysia. However, the purpose of the present research was to review and analyze the main relationships between land use and water quality, as well as to visualize the major sources and processes of water quality pollution in Malaysia.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, TSS is noted to have the highest loading followed by TN and TP for all sub-catchments. According to the previous study stated that the downstream part after Brinchang was reported to have an excessive loading of TSS especially during wet weather flow that causes more soil erosion and brings all the sediments and nutrients due to agricultural activities and residential areas [23]. Annual pollutant loads are a good indicator of the potential for impairments but consideration should be made as they do not necessarily give a complete picture of the vulnerability of a watershed to impairments caused by a particular pollutant [24].…”
Section: Music Modeling Results Without Bmps Compared With Calculatedmentioning
confidence: 99%
“…Urbanization influences ecosystems through altering water cycles [1,23,82]. The response of ET and its partitions in the QRB is one of the strongest pieces of evidence for this.…”
Section: Effects Of Land Use and Land Cover Changes On All Et Componentsmentioning
confidence: 99%
“…Urbanization-associated land use and land cover (LULC) change is a global phenomenon that has negative impacts on local environment, society, and culture [1,2]. During the urbanization processes, entire watershed water energy and balances are altered [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation